Active vibration control of planetary gears by pole placement. (July 2019) - Olanipekun, K A; Rustighi, E; Ferguson, N S
Abstract: This numerical study focuses on the assignment of poles to a planetary gear train to avoid resonance, which can cause the failure of the system. The control strategy is output feedback, which involves feeding back the displacement and velocity to achieve active stiffness and damping respectively. The reverse process was considered. This occurs when the predicted control gains were assigned by the actuators, which were placed on the translational directions of either the carrier or the sun gear bearing mounted on the shaft. In addition, the closed-loop poles were assigned in the case whereby the actuators were positioned in the translational directions of either the carrier or the sun gear. The active control was considered using both the fixed and rotating frames of reference at a carrier speed of 100 rpm. Numerical examples are presented using both reference frames with the sensors and actuators collocated. The results show that the poles of the modes with lower frequencies, which are predominantly translational modes, can be shifted while the poles of the higher modes, which are predominantly rotational remain unchanged.